2018
DOI: 10.2116/analsci.17p542
|View full text |Cite
|
Sign up to set email alerts
|

Binding Constant of the Cell-shaped Cavity Formed on a Polymer for Escherichia coli O157

Abstract: The binding constant of receptors for small molecules, proteins, or antibodies is usually determined based on the concentrations of the ligand, receptor, and their complexes. The binding constant is used as a measure of the affinity between the ligand and the receptor. In the present study, we introduce a procedure to determine the binding constant of a cell-shaped cavity formed on a polymer by molecular imprinting for a whole cell. To determine the binding constant, we clarified the numbers of cavities and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…Previously, the binding constant, Ka, was reported as 1.1 × 10 5 M -1 , which is a good binding affinity between target cells and complementary cavities. 22 Nevertheless, E. coli O rough cells having no O-antigen on their surface were captured in the vertical direction regardless of round-shaped or bacilliform cavities. Therefore, we conclude that the O-antigen-imprinted cavity worked as an artificial antibody which bound strongly to the O-antigen.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, the binding constant, Ka, was reported as 1.1 × 10 5 M -1 , which is a good binding affinity between target cells and complementary cavities. 22 Nevertheless, E. coli O rough cells having no O-antigen on their surface were captured in the vertical direction regardless of round-shaped or bacilliform cavities. Therefore, we conclude that the O-antigen-imprinted cavity worked as an artificial antibody which bound strongly to the O-antigen.…”
Section: Resultsmentioning
confidence: 99%
“…PPy was formed on nafion-coated microspheres (mean diameter: 5.0 μm) by chemical oxidation in an aqueous medium containing E. coli cells. 16,22 We supposed that cells adhered to the microspheres as the polymerization progressed and acted as dopant anions with a negative zeta potential (∼ -30 mV). SEM and fluorescence microscopy confirmed that the cells were immobilized in the PPy film ( Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polypyrrole (PPy), one of the most popular polymers among the family of conducting polymers, has superior performance such as environmental stability and biocompatibility [11]. And it can be used in many potential applications including electrode materials of supercapacitors and batteries [12][13][14], sensors [15,16], drug delivery [17,18], biological ion detection, and electromagnetic shielding materials [19].…”
Section: Introductionmentioning
confidence: 99%
“…Shan et al described determining the binding constant of the complementary cavity for a whole cell. 8 They introduce a procedure to determine the binding constant of a cell-shaped cavity formed on a polymer by molecular imprinting for a whole cell. Lv et al reported the determination of an aryl hydrocarbon receptor (AhR) coupled with anthracene (Ant) that exhibits genotoxicity and carcinogenicity based on an indirect competition enzyme linked immunosorbent assay using an AhR-Ant antibody.…”
mentioning
confidence: 99%